Aplikasi Simulated Annealing untuk Penentuan Tata Letak Mesin - Sri Kusumadewi; Hari Purnomo (Jurusan Teknik Informatika, Fakultas Teknologi Industri, Universitas Islam Indonesia, 2004)
Facilities layout has very important relation with material handling systems. One ofthe most problem in production systems is caused by unsystematic material handling. In thisresearch, we will try to implement simulated annealing algorithm to layout machines. Inputof this research are machine number, each machine dimension (length and width), sequenceof machines in each part, production volume in each part, and batch size in each part. Outputof this research is machines layout with minimum total flow cost. This research solved thecase with 15 machines and 25 parts. The result on this case is sequence of machines: 1, 12,7, 2, 4, 15, 6, 8, 11, 3, 9, 10, 14, 13 and 6 with total flow cost 6100.5.Keywords: simulated annealing, machine layout